Bridging the Rigour-Relevance Gap in Management Research: It's Already Happening - Hodgkinson, Gerard P.; Rousseau, Denise M. (Journal of management studies, 2009)
Kieser and Leiner (2009) maintain that the rigour–relevance gap in management research is fundamentally unbridgeable because researchers and the researched inhabit separate social systems. They argue that it is impossible to assess the relevance of research outputs within the system of science and that neither action research nor related approaches to collaborative research can succeed in producing research that is rigorous as well as relevant. In reply, we show how their analysis is inconsistent with available evidence. Drawing on a diversity of management research domains, we provide counter‐illustrations of work where researchers, in a number of cases in collaboration with practitioners, have generated knowledge that is both socially useful and academically rigorous.